The influence of psychological factors on Health‐Related Quality of Life after stroke: a systematic review. Issue 3 (22nd October 2013) - van, Maria L.; Schröder, Carin; van, Caroline M.; Post, Marcel W. M.; de, Paul L. M.; Visser‐Meily, Johanna M. A.
<x xml:space="preserve">Abstract</x> Background and purpose Many stroke patients experience problems with health‐related quality of life, but much of the variance of health‐related quality of life after stroke remains unexplained. Health‐related quality of life may be influenced by psychological factors, as these factors reflect the way people approach situations and react to stressful situations. The aim of this study was to systematically examine the relationship between psychological factors and health‐related quality of life after stroke. Summary of review A systematic literature search was conducted in online databases PubMed, Embase, PsycINFO, and CINAHL in November 2011. A total of nine studies were included. Personality (i.e. problems of temperament and personality functions and neuroticism) was moderately negatively associated with health‐related quality of life (r = 0·26–0·49). Coping (i.e. situational and personal adaptation), internal locus of control, self‐worth (i.e. self‐esteem and self‐efficacy), and hope and optimism were moderately positively associated with health‐related quality of life (r = 0·026–0·81). No evidence was found for an association between extraversion and health‐related quality of life. Conclusions There is still a paucity of studies on psychological determinants of poststroke health‐related quality of life. The reviewed studies supported the importance of psychological factors, but further research is needed to supplement the available evidence and to examine how psychological factors can be modified to improve health‐related quality of life, and at what moment after the stroke these interventions should be given.